Caracterización fisiológica de semillas de ocho variedades de Amaranto (amaranthus spp.) en el campus Salache, cantón Latacunga, provincia de Cotopaxi 2022. - Calapiña Tituaña, Bryan Omar (2022)
This research was conducted at the Salache campus, Latacunga canton, Cotopaxi province 2022. The aim of this research was to determine the physiological characteristics of seeds of eight varieties of amaranth (Amaranthus spp. ); Zelenaya Sosulka (T1), Bulava (T2), Diumovachka (T3), Kizliarets (T4), Fakel (T5), India (T6), Valentina (T7) and Kobaca (T8); by determining their physiological potential in each of them through a series of physiological tests such as: seed moisture, standard germination, tetrazolium, electrical conductivity, accelerated aging, cold test, emergence speed index and dry matter. For this, the methodology described by (Krzyzanowski et al., 1999), (FAO and AfrizaSeeds, 2019) and (RAS, 2009) was applied; which refer to the standards of the International Seed Testing Association (ISTA). The experimental design was a completely randomized design, with eight treatments, with four replications, giving a total of thirty-two experimental units, the statistical analyses were performed using the RStudio program. At the end of the application of the physiological tests, the results of this study revealed that all the physiological tests were able to determine the physiological profile of the eight varieties of amaranth (Amaranthus spp. ), as well as it was determined that T7 (Valentina) presented a high physiological performance, when studying the vigor and viability in all the applied tests, followed by T3 (Diumovachka) and T5 (Fakel), which presented an acceptable performance corresponding to physiological seed quality, the performance of the other treatments T1 (Zelenaya Sosulka), T2 (Bulava), T4 (Kizliarets), T6 (India) and T8 (Kobaca); were found to be inappreciable when applying the same physiological tests. As a result of this study, a practical instructive of technical specifications, materials and variations in the methodology used was developed. These instructions will be useful for future studies on physiological testing of amaranth (Amaranthus spp.) seeds and could be considered useful for working with seeds of the same or similar size, its application is adapted to the facilities of the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi.